2021
DOI: 10.1177/03000605211067125
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory and metabolic fitness indicators in novice volleyball trainees: effect of 1-week antioxidant supplementation with N-acetyl-cysteine/zinc/vitamin C

Abstract: Objectives This study aimed to determine the effect of 7-day dietary supplementation of N-acetylcysteine (NAC)/zinc/vitamin C on the time-to-exhaustion (TTE), the cardiorespiratory fitness (CRF) index, and metabolic indicators. Methods This study enrolled volleyball student trainees (n = 18 men) who took NAC/zinc/vitamin C (750 mg/5 mg/100 mg) for 7 days at Jouf University, Saudi Arabia. The CRF index and TTE were determined. Serum concentrations of metabolic regulators (insulin, betatrophin, and hepatocyte gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…They concluded that vitamin C supplementation increased plasma GSH levels, thereby enhancing the protective antioxidant effect in the blood [ 82 ]. Ascorbate administration to newborn rats with glutathione deficiency has been shown to reduce toxicity and mortality rates and increase tissue and mitochondrial glutathione levels [ 83 ].…”
Section: Vitamin C and Glutathionementioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that vitamin C supplementation increased plasma GSH levels, thereby enhancing the protective antioxidant effect in the blood [ 82 ]. Ascorbate administration to newborn rats with glutathione deficiency has been shown to reduce toxicity and mortality rates and increase tissue and mitochondrial glutathione levels [ 83 ].…”
Section: Vitamin C and Glutathionementioning
confidence: 99%
“…The effects of this supplementation on time-to-exhaustion (TTE), cardiorespiratory fitness (CRF) index, and metabolic indicators were investigated. The results indicated significant improvements in TTE and CRF following one-week supplementation with the combination of substances [ 83 ]. Although limited, previous studies have suggested that the combined supplementation of vitamin C and glutathione may exhibit additive effects compared to individual supplementation.…”
Section: Vitamin C and Glutathionementioning
confidence: 99%